2015
DOI: 10.1093/hmg/ddv399
|View full text |Cite
|
Sign up to set email alerts
|

Disruption of murineAdamtsl4results in zonular fiber detachment from the lens and in retinal pigment epithelium dedifferentiation

Abstract: Human gene mutations have revealed that a significant number of ADAMTS (a disintegrin-like and metalloproteinase (reprolysin type) with thrombospondin type 1 motifs) proteins are necessary for normal ocular development and eye function. Mutations in human ADAMTSL4, encoding an ADAMTS-like protein which has been implicated in fibrillin microfibril biogenesis, cause ectopia lentis (EL) and EL et pupillae. Here, we report the first ADAMTSL4 mouse model, tvrm267, bearing a nonsense mutation in Adamtsl4. Homozygous… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 39 publications
(46 citation statements)
references
References 79 publications
2
44
0
Order By: Relevance
“…Although most swarms comprised groups of cells, we did also note some large individual cells that were multinucleate 29,30 (Figure 5). Experimental studies in mouse demonstrated that multinucleate RPE cells in the setting of a disintegrin-like and metalloproteinase with thrombospondin type 1 motif-like 4-deficiency can be migratory 37 , suggestive of a final common pathway to different stresses, while others indicate that failed cytokinesis in cell division can cause RPE multinucleation. 38 One interesting group of intraretinal RPE appeared to follow the trajectory of Henle fiber layers, resembling a previously illustrated ‘plume’ on SD-OCT. 14 Migrating RPE cells were seen throughout all retinal layers, even surrounding inner retinal capillaries as in bone spicule degeneration, 39 a phenomenon noted in 11% of eyes in the in vivo cohort.…”
Section: Discussionmentioning
confidence: 99%
“…Although most swarms comprised groups of cells, we did also note some large individual cells that were multinucleate 29,30 (Figure 5). Experimental studies in mouse demonstrated that multinucleate RPE cells in the setting of a disintegrin-like and metalloproteinase with thrombospondin type 1 motif-like 4-deficiency can be migratory 37 , suggestive of a final common pathway to different stresses, while others indicate that failed cytokinesis in cell division can cause RPE multinucleation. 38 One interesting group of intraretinal RPE appeared to follow the trajectory of Henle fiber layers, resembling a previously illustrated ‘plume’ on SD-OCT. 14 Migrating RPE cells were seen throughout all retinal layers, even surrounding inner retinal capillaries as in bone spicule degeneration, 39 a phenomenon noted in 11% of eyes in the in vivo cohort.…”
Section: Discussionmentioning
confidence: 99%
“…), whilst ADAMTSL4 deficiency causes autosomal recessive isolated ectopia lentis (IEL) and ectopia lentis et pupillae (Collin et al . ). There is also evidence for epithelial involvement in these diseases, reminiscent of the microfibril defects seen at the dermal–epidermal junction in ‘short fibrillinopathies’ caused by fibrillin‐1 mutations.…”
Section: How Might Hs‐rich Cell Surface Zones Influence Microfibril Dmentioning
confidence: 97%
“…To better evaluate mouse models for genes expressed in the RPE, we adapted an in vivo direct current ERG (dc-ERG) procedure (Kikiwada, 1968) to monitor these responses in anesthetized mice (Wu et al, 2004b). The value of this analysis is supported by subsequent application, where mouse models have been identified in which dc-ERG abnormalities were documented in the face of normal ERG a- and b-waves (e.g., Edwards et al, 2010; Patil et al, 2014; Collin et al, 2015; Saksens et al, 2016). Basic Protocol 2 describes the approach used to record the mouse dc-ERG.…”
Section: Basic Protocolmentioning
confidence: 98%